Podvršje – Glavčine: Results of the most Recent Research - Uglešić, Ante (Hortus Artium Medievalium, 2017)
Abstract The paper offers an overview of the systematic archaeological research of the early Christian complex Glavčine in the village of Podvršje, situated about 18 km north-east of Zadar (Ražanac municipality). In eight archaeological campaigns, in the period from 2002 to 2015 a complex of double churches (geminae) with auxiliary rooms was excavated, made in two building phases in the 5th and 6th century. The early Christian complex was built at the position of an earlier round structure which is assumed to might have been a Roman temple dedicated to Syrian gods (tholos?). A smaller room with an apse also predates the building of the churches. It was built within the ruins of the round structure, and it is believed to have been an Early Christian oratory.